Familial Aggregation in Skin Flush Response to Niacin Patch Among Schizophrenic Patients and Their Nonpsychotic Relatives - Lin, Sheng-Hsiang (Oxford University Press, 2007)
Though a reduced flush response to niacin has been found in schizophrenic patients, whether it is a vulnerability indicator to schizophrenia remains little known. We aimed to examine the familial aggregation in niacin flush response among schizophrenic patients and their nonpsychotic relatives. In a sample of 153 schizophrenia probands, 217 parents, 70 siblings, and 94 normal subjects, 3 concentrations (0.001 M, 0.01 M, and 0.1 M) of niacin were applied to the forearm skin and the flush response was rated at 5, 10, and 15 minutes, respectively, with a 4-point scale. Both the heritability for continuous flush scores and the recurrence risk ratios for binary nonflush response in the nonpsychotic relatives of schizophrenic patients were estimated, and ordinal logistic regression analyses of relatives' niacin response on probands' were further conducted to adjust for potential confounders. The greatest heritabilities ranged from 47% (0.01 M at 10 minutes) to 54% (0.1 M at 5 minutes). The risk ratios of 0.01 M at 10 minutes (ranging from 2.60 for using score 1 or less to 5.06 for using score 0 as nonflush) and 5 minutes (1.66 for using score 0 as nonflush) were significantly greater than one. Multiple ordinal logistic regression analyses further revealed that the association between probands and relatives in niacin flush response remained after adjustment for potential confounders, including age, sex, allergy, tobacco smoking, and coffee drinking. These findings provide support for the potential of niacin flush response as a vulnerability indicator to schizophrenia.